Analysis of risk factors for radiation-induced oral mucositis for nasopharyngeal carcinoma and prognostic value of EGF and STREM-1 - Puyu Jiang; Po Xue; Jiani Wu (Journal of Medical Biochemistry)
Background: This study analyzed the risk factors of radiation-induced oral mucositis (RIOM) for nasopharyngeal carcinoma (NPC) and the correlation between epidermal growth factor (EGF), soluble myeloid cell expression trigger receptor-1 (sTREM-1), and disease severity. Methods: A total of 124 patients with NPC who received radiotherapy from March 2013 to November 2016 were enrolled and divided into the study group (n=68) and the control group (n=56) regarding the presence of RIOM. The risk factors of RIOM were evaluated by multivariate logistic regression. According to the severity of RIOM, patients who developed RIOM were divided into mild and severe groups, and the correlation between EGF, sTREM-1 and the severity of RIOM was analyzed by linear regression. According to the 5-year survival of patients after treatment, they were divided into a poor prognosis group (death, recurrence, and distant metastasis) and a better prognosis group and the predictive value of the prognosis of patients was analyzed by the ROC curve. Results: Age (>55 years), smoking, poor oral hygiene, and oral pH<7 were risk factors for RIOM, and the use of oral mucosal protective agents was a protective factor (P<0.05). In patients who developed RIOM, EGF levels decreased with increasing severity of RIOM, and sTREM-1 levels increased (P<0.05). The EGF level of patients was negatively correlated with the severity of RIOM. In addition, EGF levels in the poor prognosis group were lower than those in the better prognosis group, whereas sTREM-1 levels were higher than those in the better prognosis group (P<0.05). The AUC of the combined EGF and sTREM-1 levels test for predicting a patient's prognosis was greater than that of sTREM-1 alone (P<0.05). Conclusions: In short, age (>55 years), smoking, poor oral hygiene, and oral PH<7 are risk factors for RIOM for NPC. The use of oral mucosal protective agents is a protective factor. EGF and sTREM-1 levels are associated with RIOM severity and indicate predictive values for patient outcomes. This study provides new ideas for mitigating the occurrence of RIOM after radiotherapy to treat NPC.